The South African National War College military history staff ride as a deep learning experience - Jacobs, James Jacobs; Wassermann, Johan (Scientia Militaria - South African Journal of Military Studies, 2021)
In this article, based on a study rooted in interpretivism, the South African National War College military history staff ride, as an education and training method related to the curriculum of the senior staff programmes since 2002, is discussed. The education and training process, with specific reference to the staff ride to military battle sites and the associated application of the theory of operational art, were researched according to the tenets of the theory of deep learning. While using the historical–comparative method during the staff ride enabled the majority of the students to determine which viable options were available to the commander, not all students were necessarily able to relate deep learning to critical thinking. Consequently, in certain instances, surface learning tended to dominate simply because that was the educational world into which the students had been socialised. Furthermore, the facilitation process did not always fully serve the students by completely weaning them off learning habits associated with surface learning. Consequently, while being able to claim some deep learning successes using the staff ride, continuous reflection and educational interventions are needed to maintain the successes achieved and to use these as a building platform for deep learning during future staff rides.